Suppression of menstruation in adolescents with severe learning disabilities. Issue 7 (22nd June 2007) - Albanese, Assunta; Hopper, Neil W
Abstract : As girls with severe cognitive developmental delay progress into puberty and become young women with learning disabilities, concerns about menstruation are common amongst carers and health care professionals are often consulted for advice. Very little, however, has been published on this area to guide the practitioner and studies are almost exclusively confined to the gynaecological literature. We aim to give an account of the various therapeutic options available and current practice within the paediatric endocrinology unit at our institution.